Francis Bacon : new studies : centenary essays - Harrison, Martin (Göttingen : Steidl, 2009)
Preface / [Martin Harrison] ## Bacon's spiritual realism-the spirit in the body / Darren Ambrose ## Bacon and Lerski : a possible dialogue / Richard Calvocoressi ## Francis Bacon and Walter Sickert; 'Images which unlock other images' / Rebecca Daniels ## Interviewing Bacon, 1973 / Hugh M. Davies ## Francis Bacon's alter ego? Critical remarks on the Barry Joule collection / Marcel Finke ## Painting, smudging / Martin Harrison ## Francis Bacon, medievalist? / Andrew R. Lee ## Francis Bacon, trash and complicity / Brenda Marshall ## 'The mystery of paint' : Francis Bacon's materials / Joanna Russell.
Onderzoek KASK Professioneel (OFVP)
boek
Keywords: Bacon, Francis